The Physical Property Changes of Peatland upon Conversion of Oil Palm Plantation to Corn Cropping in Kinali, West Pasaman, West Sumatera - Mimien Harianti; Teguh Budi Prasetyo; Junaidi Junaidi; Gusmini Gusmini; Anggun Fitria Yenad (Jurnal Ilmu Pertanian Indonesia, 2022)
The decrease in oil palm production in Kinali, West Pasaman Regency, has become the factor that makes the farmers convert their peatlands to corn cropping. This study aimed to examine the physical characteristics (irreversible drying) of peatlands due to the conversion of oil palm to corn cropping. Some observations and samplings were conducted by applying a transect method, as it was perpendicular to the collection drain for 2, 200, and 400m from the main drains in three locations as the uses of the lands: (1) oil palm plantations, (2) <2-year corn cropping, (3) >2-year corn cropping. In each land, 3 sample points were taken with 2 repetitions at a depth of 0‒20 cm and 20‒40 cm. The physical properties of peatlands that have been converted from oil palm plantations to corn cropping include the water content increasing from 286.4 to 348.5 and 322.7%, the ash content decreasing from 55.2 to 43.5 and 47.5%, with C-organic increased by 25.9 to 30.7 and 32.4%, fiber content increased from 27.1 to 32.1 and 28.7%, and the volume weight of the peat tended to be similar (0.3 g/cm3). In all land use, irreversible drying occurred; in the oven at 50°C dan 70°C with a drying time of 3´24 hours, and at 150°C, and the drying time of 1´24 hours, the moisture content of 232‒256% in oil palm plantation, 269‒290% in <2-year corn cropping, and 394‒440% in >2-year corn cropping. Irreversible drying occureds more quickly on the peatlands in oil palm plantations rather than in corn cropping. Keywords: corn cropping, irreversible drying, palm oil plantation, peatland